The effect of Sol-Gel technique on the aluminium-SiCp composite - Idris, Jamaliah; Nee, N. J. (Faculty of Mechanical Engineering, Universiti Teknologi Malaysia, 2005)
Due to the low reactivity between the silicon carbide particulate (SiCp) and Aluminium (Al) interface bonding strength, SiCp is treated by applying a coating on its surface. The objective of this paper is to study the effect applying ceramic sol coating, which is silica sol via sol gel technique onto SiCp. The various concentrations applied are 2 wt%, 4 wt% and 10wt% of silica sol. Aluminium metal matrix composite (Al-MMC) reinforced with 10% and 20% volume fraction of SiCp produced by powder metallurgy technique with sintering temperature of 550°C was studied. The surface morphology of Al-MMC is observed using SEM to examine the particle distribution, porosity and flow pattern. While the degradation of SiCp due to interfacial reaction between the particulate and Al matrix is examined by x-ray diffraction (XRD). SiCp degradation is evaluated by the ratio of the SiC to the silicon (Si) XRD peak. From microstructure analysis, the specimens coated with 2 wt% and 4 wt% silica sol coating showed the best result which has uniform reinforcement distribution, lower porosity and better flow pattern. For XRD analysis, the best coating was obtained by 4 wt% silica sol concentration that has greater reaction between Al and SiC.